Seagrass Carbon Stock Variability Across Contrasting Coastal Areas on Pari Island, Indonesia - Bima Faqih Ramadhan; Yonvitner; Fery Kurniawan (Coastal and Ocean Journal (COJ), 2026)
Seagrass meadows are important blue carbon ecosystems, yet integrated estimates of biomass and sediment carbon stocks in small tropical islands remain limited. This study quantified total ecosystem carbon stock in seagrass meadows of Pari Island, Thousand Islands, Jakarta, and compared carbon storage between developed and natural coastal areas. Field sampling was conducted at four stations representing contrasting coastal use settings. Seagrass ecological parameters were assessed using a line transect quadrat, while aboveground biomass, belowground biomass, and sediment carbon stocks were estimated using the Loss on Ignition (LOI) approach. Sediment cores were collected and analyzed across representative depth intervals to estimate profile-based carbon storage. Mean total ecosystem carbon stock was 118.08 Mg C ha-1, ranging from 83.15 Mg C ha-1 to 135.46 Mg C ha-1 among stations. Sediment was the dominant carbon pool, contributing approximately 92-96% of the total carbon stock in the ecosystem, whereas biomass contributed less than 8%. Undisturbed areas showed higher mean sediment carbon stock than anthropogenic areas, although the difference was not statistically significant. In contrast, anthropogenic areas exhibited greater spatial variability in carbon storage. These results show that seagrass meadows in Pari Island function as important blue carbon reservoirs and underscore the importance of sediment integrity in maintaining ecosystem carbon storage.